Comparison of the Effect of Variable Helix Angle Geometry Tools on CNC Vertical Milling Machines on Chatter using a microcontroller Based on SLD - Simon, Christof Geraldi; Hardinsi, Festo Andre; Paliling, Formanto (Politeknik Negeri Ujung Pandang, 2023)
Vibrations that often occur in the production process using CNC milling machines are very important to take into account. These vibrations can cause dimensional changes and affect the level of quality produced, so the effect of chatter vibrations on production becomes a major problem in the milling process. Vibration values are determined using SLD graphs experimentally, analytically and semi-analytically. The material used in this study is SS 304, MPU 6050 which is connected to Arduino Uno using LabVIEW 2019 student edition software in the form of FFT charts. Data collection using experimental methods, tool geometry parameters are tool geometry VHA 35/38 degrees and VHA 36/38 (Degrees), Spindle Speed 2000,2500,3000 (RPM), Depth Of Cut 0.4, 0.7, 1 (mm), and Feed Rate 100, 125 and 150 (mm/s). The results of the SLD study used a variable helix angle of 35/38 degrees at a feed rate variation of 100 mm / minute chatter at cut depths of 1, 0.7 and 0.7 mm, at a feed rate variation of 125 mm / minute chatter at a cut depth of 0.7, 1 and 0.7 mm. At feed rates of 150 mm/min at cut depths of 1, 1, and 0.7 mm with spindle speeds equal to 2000.2500 and 3000 RPM. While VHA results of 36/38 degrees at a feed rate of 100 mm / minute experienced chatter at cut depths of 0.7.1 and 1 mm, at feed rates of 125 mm / minute chatter at cut depths of 1.1 and 0.7 mm. At a feed rate variation of 150 mm/min chatter at cut depths of 1.1, and 0.7 mm with the same spindle speeds of 2000.2500 and 3000 RPM.Keywords : Chatter, VHA, SLD, microcontrolle, FFT